KONTROL 3D PRINTER BERBASIS ARDUINO - Reza Pahlevi; Muhammad Boby Kusnadi; Made Andik Setiawan; Charlotha Charlotha (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Currently the industrial world continues to experience development, especially industries engaged in manufacturing. Product development by manufacturing companies is a must to meet consumer needs. One of the most efficient ways to develop these products is to use a 3D printer. The 3D printers on the market use the RAMPS 1.4 control board with the marlin firmware which is open source, while the 3D printers made use of the Arduino as the control system. This 3D printer has the ability to print straight lines with the Matlab application as an application to give commands to print. To get maximum results, it is necessary to prepare and test to get the appropriate parameters. Based on the testing of the tools that have been made, the 3D printer can function sufficiently with parameters such as nozzle temperature in the range of 150 ℃ and the distance between the nozzle tip and the print bed of 0.25 mm. The 3D printer that has been made has an accuracy rate of ± 9.4 mm with a resolution of 0.16 mm and a repitability of 0.2 mm.